PRINCIPLES AND GUIDELINES FOR THE IMPLEMENTATION OF BIOECONOMY STRATEGIES - P. Branzova (Trakia Journal of Sciences)
The report examines existing bioeconomy strategies. The principles and guidelines of the individual countries for the implementation of the strategies are considered. A comparative analysis of the strategies was made. Based on this, the principles and guidelines for the implementation of the strategies for the bioeconomy of individual countries are derived.